2015
DOI: 10.1097/mpg.0000000000000679
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Procedures Update on Hirschsprung Disease

Abstract: Hematoxylin and eosin with or without acetylcholinesterase remains the criterion standard according to our PRISMA-based data. In our opinion, the number of false-positive results with potential overtreatment may limit the increasing advocacy for calretinin staining. Both the "primum non nocere" dictum and the "loss aversion heuristic" need to be satisfied harmoniously by preventing harm from unnecessary surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
49
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 49 publications
2
49
1
Order By: Relevance
“…Hirschprung's disease (HSCR; MIM# 142623), one disorder of the ENS, is a rare congenital developmental disorder of the gastrointestinal tract characterized by a failure of vagal system derived enteric neural crest (NC) cells (ENCC) (neurocristopathy) to fully migrate cranio-caudally during embryonic development and adequately colonize the entire gut, leaving an aganglionic portion of variable length (6)(7)(8)(9). Although original studies suggested colonization of the entire length of the human gut by enteric neural precursors is not complete until the 12th week of gestation, more recent studies seem to support complete colonization by the 7th week, which corresponds more closely with data obtained from animal models as well (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hirschprung's disease (HSCR; MIM# 142623), one disorder of the ENS, is a rare congenital developmental disorder of the gastrointestinal tract characterized by a failure of vagal system derived enteric neural crest (NC) cells (ENCC) (neurocristopathy) to fully migrate cranio-caudally during embryonic development and adequately colonize the entire gut, leaving an aganglionic portion of variable length (6)(7)(8)(9). Although original studies suggested colonization of the entire length of the human gut by enteric neural precursors is not complete until the 12th week of gestation, more recent studies seem to support complete colonization by the 7th week, which corresponds more closely with data obtained from animal models as well (10).…”
mentioning
confidence: 99%
“…When suspected, HSCR is diagnosed by standard histopathological evaluation with or without auxiliary special stains or immunohistochemistry that confirms the diagnosis following biopsy of the distal rectum (Figure 1a-c). Expression of calretinin, a vitamin D-dependent calcium-binding protein found in ganglion cells and nerves, has been described as an adjunctive or primary diagnostic test on gut biopsy specimens in HSCR with lack of specific calretinin staining confirming the diagnosis of aganglionosis (Figure 1d) (8). Classifying HSCR clinically is not an easy task, because the nervous system colonization failure may be variable or discontinuous (9,(13)(14)(15).…”
mentioning
confidence: 99%
“…The diagnostic evaluation of HD consists of a contrast enema, anorectal manometry, and rectal biopsy. Of these, contrast enema and anorectal manometry are not confirmatory, and rectal biopsy is required to confirm the diagnosis . In our study, rectoanal inhibitory reflex (RAIR) was absent in a majority of the children undergoing rectal biopsy.…”
Section: Discussionmentioning
confidence: 64%
“…Various techniques have been described to procure rectal biopsy. These include suction biopsy, full‐thickness rectal biopsy, and biopsy with a jumbo forceps . Rectal suction biopsy is the most preferred sampling technique for the diagnosis of HD.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the immune system, as well as the pulmonary and gastrointestinal organs, remain difficult to manage. At this age an increased rate of infection has been identified, and gastrointestinal dysfunction is common [1][2][3][4][5][6]. Cardiovascular function and sepsis are intimately related and may trigger early death without NICU or PICU intervention [7].…”
mentioning
confidence: 99%